2019
DOI: 10.1021/acs.joc.9b00842
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Driven Chlorotrifluoromethylative and Chlorotrichloromethylative Cyclizations of Enynes

Abstract: Described herein is a visible-light-driven chlorotrifluoromethylative and chlorotrichloromethylative cyclization reaction to synthesize chlorotrifluoromethylated and chlorotrichloromethylated cyclic compounds. Visible-light photochemistry was utilized to generate trifluoromethyl and trichloromethyl radicals and trigger radical addition/cyclization/chlorination sequences. The use of terminal alkene-derived enynes enables the regioselective and stereoselective synthesis of chlorotrifluoromethylated and chlorotri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…In our previous studies on the atom transfer radical cyclization (ATRC) reactions, various chlorinated cycles were synthesized under the visible-light photoredox catalysis conditions, and the results indicated that the chlorine atom of sulfonyl chlorides could be transfer under metal-free conditions, but the bromine atom failed to transfer into the final products from the bromodifluoroacete ester . In continuation of our research on the ATRC reactions, we herein report an example of bromodifluoroacetylative cyclization reactions by use of copper as catalyst where a variety of valuable alkenyl C–Br bonds containing functionalized heterocycles were obtained.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…In our previous studies on the atom transfer radical cyclization (ATRC) reactions, various chlorinated cycles were synthesized under the visible-light photoredox catalysis conditions, and the results indicated that the chlorine atom of sulfonyl chlorides could be transfer under metal-free conditions, but the bromine atom failed to transfer into the final products from the bromodifluoroacete ester . In continuation of our research on the ATRC reactions, we herein report an example of bromodifluoroacetylative cyclization reactions by use of copper as catalyst where a variety of valuable alkenyl C–Br bonds containing functionalized heterocycles were obtained.…”
mentioning
confidence: 87%
“…It should be mentioned that the high Z / E selectivity benefitted from the steric effects of the gem -alkyl groups, terminal aryl groups, and heteroatom or groups containing enynes …”
mentioning
confidence: 99%
“…Following a similar strategy but using enynes instead of simple olefins, a cascade cyclization of enynes was recently reported by Hou, Chen, and Zhu’s group. Thus, a new visible-light-mediated photocatalytic chlorotrifluoromethylation and chlorotrichloromethylation of 1,6-enynes 31 in the presence of CX 3 SO 2 Cl (X= F, Cl) is described [ 50 , 51 ]. The process proceeds through an initial radical addition, followed by a cyclization/chlorination sequence.…”
Section: Chloro- and Bromotrifluoromethylationmentioning
confidence: 99%
“…Moreover, non-metallic photocatalysts such as organo-photocatalyst were also developed. For example, in 2019, Zhu et al described a visible-light-driven chlorotrifluoromethylative and Molecules 2021, 26, 6781 2 of 9 chlorotrichloromethylative cyclization approach by using organo-photocatalysts; a series of chlorotrifluoromethylated and chlorotrichloromethylated pyrrolidines, piperidines, and cyclopentanes were obtained in moderate to good yields [20]. Additionally, a visiblelight-mediated intermolecular radical cyclization approach to access the heterocycle was developed by using Eosin Y as the catalyst for the hydrogen atom transfer [21].…”
Section: Introductionmentioning
confidence: 99%
“…dines, piperidines, and cyclopentanes were obtained in moderate to good yields [20]. Additionally, a visible-light-mediated intermolecular radical cyclization approach to access the heterocycle was developed by using Eosin Y as the catalyst for the hydrogen atom transfer [21].…”
Section: Introductionmentioning
confidence: 99%